Synthesis of 4-(2-fluorophenyl)-7-methoxycoumarin: experimental and computational evidence for intramolecular and intermolecular C–F···H–C bonds - Mzozoyana, Vuyisa; van Heerden, Fanie R.; Grimmer, Craig (Beilstein Journal of Organic Chemistry, 2020)
4-(2-Fluorophenyl)-7-methoxycoumarin (6) was synthesized by Pechmann reaction under mild conditions via a three-step reaction. The solution-state 1H NMR spectra of 6 showed a strong intramolecular interaction between F and H5 (JFH = 2.6 Hz) and 13C NMR suggested that this C–F···H–C coupling is a through-space interaction. The 2D 19F-{1H} HOESY and 1H-{19F} 1D experiments were done to confirm this F···H interaction. The single crystal X-ray structure and the DFT-optimized structure showed that the fluorinated phenyl ring favors the orientation with the fluorine atom closer to H5 than H3. The X-ray structure also showed the existence of the intermolecular C–F···H–C interaction.
Keywords: DFT; F···H hydrogen bond; fluorinated phenylcoumarin; Pechmann reaction; through-space coupling

(untitled) - Lin, M.-H.; Chou, Y.-S.; Tsai, Y.-J.; Chou, D.-S. (J. Exp. Clin. Med., 2011)

(untitled) - Hoult, J. R. S.; Payá, M. (Gen. Pharmacol.: Vasc. Syst., 1996)

(untitled) - Hara, K.; Sayama, K.; Ohga, Y.; Shinpo, A.; Suga, S.; Arakawa, H. (Chem. Commun., 2001)

(untitled) - Givel, M. (Tob. Control, 2003)

(untitled) - Emmanuel-Giota, A. A.; Fylaktakidou, K. C.; Litinas, K. E.; Nicolaides, D. N.; Hadjipavlou-Litina, D. J. (J. Heterocycl. Chem., 2001)

(untitled) - Marchenko, M. M.; Kopyl’chuk, G. P.; Shmarakov, I. A.; Ketsa, O. V.; Kushnir, V. N. (Pharm. Chem. J., 2006)

(untitled) - Vukovic, N.; Sukdolak, S.; Solujic, S.; Niciforovic, N. (Arch. Pharmacal Res., 2010)

(untitled) - Basanagouda, M.; Kulkarni, M. V.; Sharma, D.; Gupta, V. K.; Pranesha; Sandhyarani, P.; Rasal, V. P. (J. Chem. Sci., 2009)

(untitled) - Jung, K.; Park, Y.-J.; Ryu, J.-S. (Synth. Commun., 2008)

(untitled) - Vilar, S.; Quezada, E.; Santana, L.; Uriarte, E.; Yánez, M.; Fraiz, N.; Alcaide, C.; Cano, E.; Orallo, F. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Maheswara, M.; Siddaiah, V.; Damu, G. L. V.; Rao, Y. K.; Rao, C. V. (J. Mol. Catal. A: Chem., 2006)

(untitled) - Cherry, K.; Parrain, J.-L.; Thibonnet, J.; Duchêne, A.; Abarbri, M. (J. Org. Chem., 2005)

(untitled) - Heravi, M. M.; Hekmatshoar, R.; Emamgholizadeh, M. (Phosphorus, Sulfur Silicon Relat. Elem., 2004)

(untitled) - Barancelli, D. A.; Salles, A. G., Jr; Taylor, J. G.; Correia, C. R. D. (Org. Lett., 2012)

(untitled) - Kaye, P. T.; Musa, M. A. (Synthesis, 2002)

(untitled) - Ray, S. K.; Singh, P. K.; Molleti, N.; Singh, V. K. (J. Org. Chem., 2012)

(untitled) - Jung, J.-W.; Kim, N.-J.; Yun, H.; Han, Y. T. (Molecules, 2018)

(untitled) - Wu, J.; Liao, Y.; Yang, Z. (J. Org. Chem., 2001)

(untitled) - Fried, J.; Sabo, E. F. (J. Am. Chem. Soc., 1954)

(untitled) - Hagmann, W. K. (J. Med. Chem., 2008)

(untitled) - Barradell, L. B.; Faulds, D.; McTavish, D. (Drugs, 1992)

(untitled) - Gether, U.; Andersen, P. H.; Larsson, O. M.; Schousboe, A. (Trends Pharmacol. Sci., 2006)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - O'Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Isanbor, C.; O’Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

(untitled) - Beijer, F. H.; Kooijman, H.; Spek, A. L.; Sijbesma, R. P.; Meijer, E. W. (Angew. Chem., Int. Ed., 1998)

(untitled) - Duarte, C. J.; Freitas, M. P. (J. Mol. Struct., 2009)

(untitled) - Fonseca, T. A. O.; Freitas, M. P.; Cormanich, R. A.; Ramalho, T. C.; Tormena, C. F.; Rittner, R. (Beilstein J. Org. Chem., 2012)

(untitled) - Nath, B.; Baruah, J. B. (Cryst. Growth Des., 2013)

(untitled) - Ridout, J.; Probert, M. R. (Cryst. Growth Des., 2013)

(untitled) - Murray-Rust, P.; Stallings, W. C.; Monti, C. T.; Preston, R. K.; Glusker, J. P. (J. Am. Chem. Soc., 1983)

(untitled) - Desiraju, G. R. (Acc. Chem. Res., 2002)

(untitled) - Howard, J. A. K.; Hoy, V. J.; O'Hagan, D.; Smith, G. T. (Tetrahedron, 1996)

(untitled) - Pedireddi, V. R.; Desiraju, G. R. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Thakur, T. S.; Kirchner, M. T.; Bläser, D.; Boese, R.; Desiraju, G. R. (CrystEngComm, 2010)

(untitled) - Shang, J.; Gallagher, N. M.; Bie, F.; Li, Q.; Che, Y.; Wang, Y.; Jiang, H. (J. Org. Chem., 2014)

(untitled) - Jeon, M.-K.; Kim, K. (Tetrahedron, 1999)

Synthesis of fluorinated benzophenones and phenylcoumarins - Mzozoyana, V. (UKZN, 2015)

(untitled) - Hirschberg, J. H. K. K.; Koevoets, R. A.; Sijbesma, R. P.; Meijer, E. W. (Chem. – Eur. J., 2003)

(untitled) - Anwar, H. F. (Synlett, 2009)

(untitled) - Panetta, J. A.; Rapoport, H. (J. Org. Chem., 1982)

(untitled) - Raad, I.; Terreux, R.; Richomme, P.; Matera, E.-L.; Dumontet, C.; Raynaud, J.; Guilet, D. (Bioorg. Med. Chem., 2006)

(untitled) - Timonen, J. M.; Nieminen, R. M.; Sareila, O.; Goulas, A.; Moilanen, L. J.; Haukka, M.; Vainiotalo, P.; Moilanen, E.; Aulaskari, P. H. (Eur. J. Med. Chem., 2011)

Gaussian 16, Revision C.01 (Gaussian, Inc., 2016)

(untitled) - Agranat, I.; Rabinovitz, M.; Gosnay, I.; Weitzen-Dagan, A. (J. Am. Chem. Soc., 1972)

(untitled) - Adcock, W.; Rizvi, S. (Aust. J. Chem., 1973)

(untitled) - Malkina, O. L.; Salahub, D. R.; Malkin, V. G. (J. Chem. Phys., 1996)